Monetary Policy Regimes, Expected Inflation, and the Response of Interest Rates to Money Announcements - Roley, V. Vance; Walsh, Carl E. (Quarterly Journal of Economics, 1985)
V. Vance Roley, Carl E. Walsh, Monetary Policy Regimes, Expected Inflation, and the Response of Interest Rates to Money Announcements, The Quarterly Journal of Economics, Vol. 100, Supplement (1985), pp. 1011-1039